A prospective single‐centre evaluation of the intra‐individual variability of faecal calprotectin in quiescent Crohn's disease. Issue 6 (24th January 2013) - Naismith, G. D.; Smith, L. A.; Barry, S. J. E.; Munro, J. I.; Laird, S.; Rankin, K.; Morris, A. J.; Winter, J. W.; Gaya, D. R.
Summary Background As a non‐invasive marker of gastrointestinal inflammation, faecal calprotectin (FC) is being increasingly used to guide the management of Crohn's disease. It is therefore a concern that studies have shown variability in day to day levels. Aim To determine the degree of this intrapersonal variability in the context of quiescent Crohn's disease. Methods A single‐centre prospective study was undertaken in 143 Crohn's disease patients in clinical remission. Three faecal calprotectin levels were analysed from stool samples on consecutive days. Consistency of faecal calprotectin levels was determined by measuring the intraclass correlation (ICC). Due to higher variability at higher faecal calprotectin levels, the ICC was calculated for the log‐transformed values. The reliability of detecting a 'case' of active inflammation as defined for specific concentrations of faecal calprotectin was measured by the kappa statistic. Results Ninety‐eight complete sets of results were obtained. The ICC was 0.84 (95% CI: 0.79–0.89), which represents low variability across samples. The kappa statistic for the reliability of detecting a case as defined by an FC level of >50 μg/g was substantial at 0.648 (0.511–0.769). Conclusions Day to day variability of faecal calprotectin is low in our cohort of quiescent Crohn's disease patients and the reliability of defining a 'case' is moderately good. These data provide reassurance to clinicians using a single calprotectin sample to inform therapeutic strategies in this cohort.